Condicionantes geofísicos de los usos del territorio en un valle de la montaña cantábrica - Alvarez J.; Yanguas M.M.; Rodríguez M.A.; Gómez Sal A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The territorial distribution of traditional uses and their relationship with the geophysical structure of the land are analysed. Plots of land were classified after systematic sampling and this made it possible to differentiate homogeneous areas as regards physical environment conditions. The greatest differences appear between convex relief export areas and reception and accumulation areas. Pasture composition corresponds well with the detected areas, although only one of the areas (that of low-lying terrain) seems to show well-defined characteristics as regards discriminating species.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)